Does gender equality affect municipal transparency: the case of Spain - Araújo, Joaquim Filipe (2018)
The influence of women in organizational transparency is an understudied vein of representative bureaucracy. Literature claims that the increase of women in formal political representation opened the opportunity to bring to public organizations gender diversity, experiences, and values different from those of men. It highlights the beneficial leadership styles and the legitimacy of public bureaucracies. Since gender equality in Spanish local government has increased in recent years, it was the trigger and the aim for this study: to understand the influence of women’s political representation on the level of Spanish municipalities’ transparency. The analysis draws on panel data econometric techniques. The results reinforce the discussion that the representation of women in local political life will increase information transparency and reduce information asymmetry in municipalities.